Continuous production of a multi-filament reinforced metal matrix composite strip from the semisolid state - De Pádua Lima Filho, Antonio [UNESP]; Ikeda, Rafael Shoiti [UNESP]; De Castro, Tales Paschoalino [UNESP]; Filho, Ricardo Luiz Pugina [UNESP] (My University, 2014)
Continuous metal matrix composite strip casting (MMCS-ing) composed of six 0.3-mm diameter annealed bare copper wires in a eutectic SnPb matrix was manufactured by a two-roll melt dragged processing (TRMD-ing) method at a rate of 0.3 m/s. The wires were dragged through a semisolid pool with a fibre contact time of approximately 0.2 s. The required gap between rolls to thixoforge the semisolid material around the wire filaments was approximately 1.4 mm. A successful continuous composite strip casting was achieved with a notably good degree of wire alignment. No cracks were observed at the copper wire/matrix interface. However, regions of porosity occurred in the matrix; their possible formation mechanisms are discussed. The solidification structure of the matrix was analysed, and the analysis results indicated the formation of small globular grains measuring approximately 3 µm in diameter. The specimens were evaluated for their tensile properties and compared with the rule of mixtures. The surface fracture analysis indicated a good matrix/fibre union. MMCS-ing is an economically viable process and has significant advantages over other metal matrix composite (MMC) fabrication methods.
Keywords: Metal matrix composites; Metallic fibres; SnPb alloys; Strip casting